Non–Small Cell Lung Carcinoma: Clinical Reasoning in the Management of a Patient Referred to Physical Therapy for Costochondritis. Issue 6 (18th January 2018) - Hensley, Craig P; Emerson, Alicia J
Abstract: Background and Purpose: Chest pain, a frequent complaint for seeking medical care, is often attributed to musculoskeletal pathology. Costochondritis is a common disorder presenting as chest pain. Initial physical therapist examination emphasizes red flag screening. Reexamination throughout the episode of care is critical, particularly when patients are not progressing and/or in the presence of complex pain presentations. The purpose of this case report is to describe the clinical reasoning process in the management of a patient referred to physical therapy with a medical diagnosis of costochondritis. Case Description: A 59-year-old woman presented with a 5-month history of left–sided chest pain that had progressed to include the cervical and shoulder regions. She reported multiple psychosocial stressors; a depression screen was positive. She reported a history of asthma and smoking and improvement in recent fatigue, coughing, dyspnea, and sweating. At the initial visit, shoulder, cervical, and thoracic active and passive range of motion and joint mobility testing reproduced her pain. Allodynia was present throughout the painful areas in the left upper quarter. Outcomes: The patient demonstrated improvement over 30 days (4 visits). On her fifth visit (day 35), she reported an exacerbation of her chest and upper extremity pain and noted increased fatigue, sweating, dyspnea, and loss of appetite. Even though her pain was again reproduced with musculoskeletal testing, the physical therapist contacted the patient's physician regarding the change in presentation. A subsequent chest computed tomography scan revealed a non–small cell lung adenocarcinoma. Discussion: Cancer can masquerade as a musculoskeletal condition. This case highlights the importance of screening, clinical reasoning, and communication throughout the episode of care, particularly in the presence of chronic pain and psychosocial stressors.